Posttranslational control of HuR function - Ioannis Grammatikakis; Kotb Abdelmohsen; Myriam Gorospe (2016)
The RNA ‐binding protein HuR (human antigen R) associates with numerous transcripts, coding and noncoding, and controls their splicing, localization, stability, and translation. Through its regulation of target transcripts, HuR has been implicated in cellular events including proliferation, senescence, differentiation, apoptosis, and the stress and immune responses. In turn, HuR influences processes such as cancer and inflammation. HuR function is primarily regulated through posttranslational modifications that alter its subcellular localization and its ability to bind target RNAs ; such modifications include phosphorylation, methylation, ubiquitination, NEDDylation , and proteolytic cleavage. In this review, we describe the modifications that impact upon HuR function on gene expression programs and disease states. WIREs RNA 2017, 8:e1372. doi: 10.1002/wrna.1372 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Recognition RNA Interactions with Proteins and Other Molecules > RNA–Protein Complexes